1973
DOI: 10.2307/1158544
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Reconsidered: Some Historical Aspects of Religious Conversion in Black Africa

Abstract: Opening ParagraphThis paper had its genesis in the recent thoughtful and stimulating article by Robin Horton, on African conversion; the core of his argument is summarized below. Horton's evidence is chiefly drawn from Christian African experience, though he seeks to generalize from it for both Islam and Christianity. My specific purpose here is to look more closely at the phenomenon of Muslim conversion, and to see what light this may throw on Horton's argument. In particular, he has, I think, over-estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(30 citation statements)
references
References 5 publications
0
28
0
2
Order By: Relevance
“…african societies as well as their traditions and thoughts were influenced by their encounter with european colonists and white missionaries, starting a slow journey towards what the strangers called 'modernity'-a journey which robin horton argues, with some success, would have occurred regardless of the arrival of the two world religions (horton 1971; 1975a; 1975b). horton's thoughts are of interest, particularly in terms of the more recent debate on the turns in history which moved societies towards development of a global consciousness; however, horton was criticised for not being able to convincingly identify the elements within the african culture which, regardless of islamic, Christian, or colonial presence, moved society in this direction (Fisher 1973). this brief look at traditional religion in the region has thus shown that religion throughout history has been an important aspect of social organisation in northern Cameroon, but that the religious practices were, in principle, limited to the ethnic group in question. particularism was the main focus of the practices; the time aspect was oriented backwards towards the ancestors while the space dimension was directed towards the physical surroundings of the village.…”
Section: African Roots and Arab Influencementioning
confidence: 99%
“…african societies as well as their traditions and thoughts were influenced by their encounter with european colonists and white missionaries, starting a slow journey towards what the strangers called 'modernity'-a journey which robin horton argues, with some success, would have occurred regardless of the arrival of the two world religions (horton 1971; 1975a; 1975b). horton's thoughts are of interest, particularly in terms of the more recent debate on the turns in history which moved societies towards development of a global consciousness; however, horton was criticised for not being able to convincingly identify the elements within the african culture which, regardless of islamic, Christian, or colonial presence, moved society in this direction (Fisher 1973). this brief look at traditional religion in the region has thus shown that religion throughout history has been an important aspect of social organisation in northern Cameroon, but that the religious practices were, in principle, limited to the ethnic group in question. particularism was the main focus of the practices; the time aspect was oriented backwards towards the ancestors while the space dimension was directed towards the physical surroundings of the village.…”
Section: African Roots and Arab Influencementioning
confidence: 99%
“…In disagreeing with Weber, Horton (1971, 1975a, 1975b) sparked a debate on African conversion with his ‘Intellectualist Theory’ by insisting that ‘traditional religions’ are no less rational than ‘world religions’, just narrower in focus. This led to a famous dialogue with Fisher (1973, 1985) and others (Ifeka-Moller 1974, Ikenga-Metuh 1987). Horton's theory continues to be debated today, especially by scholars examining conversion in Africa (Aguilar 1995, Comaroffs 1991, Gabbert 2001, Hamer 2002, Peel 2000, Ranger 1993, Searing 2003).…”
Section: Conversion To Modernitiesmentioning
confidence: 99%
“…Just as literacy elsewhere and at other times has served as a time bomb of reform (Fisher 1973), and has enabled the forging of connections with congregations from afar (Ranger 1993) or even within the same nation (Anderson 1998), Shi`i texts provide alternative answers to questions about Islam. Augis (2002) argues that Muslims who make an intrafaith conversion are reading the Qur'an for the first time as a result of participating in reformist organizations that advocate Qur'anic literacy.…”
Section: Conversion To Modernitiesmentioning
confidence: 99%
“…Sipho recounted in his interview with me that there had been conflicts over who had the right to collect funds for the mosque at the time. The alleged use of the term "kafir" and "munafiq" on the part of the imam does not seem entirely consist- Horton (1971), Fisher (1973.…”
Section: A "Moral Values Survey" Conducted By the Human Sciences Resementioning
confidence: 99%